Rancang Bangun Spaced Repetition Software untuk Menghafal Huruf Jepang Menggunakan Algoritma Supermemo 2 Berbasis IOS - Agustyan Hidayat; Ni Made Satvika Iswari (ULTIMA InfoSys, 2018)
During the study of another language such as Japanese, the problem that exists is in remembering each of the characters that is used as writing mechanism. This is happened because the difference with Roman characters and the number of character that exist, is far beyond that of alphabet which makes a visual impairment for those used to write in alphabet. There is a traditional way to remember something which is periodically learn or remember the characters and assign a visual image to each of the characters in order to be remembered easily. Spaced repetition is a method that give an interval during a repetition which is mainly used for someone who want to remember something periodically by learning it for a long term periodically. This research discusses the implementation of one of spaced repetition algorithm called SuperMemo 2 and using it along with a flashcard to learn Japanese characters periodically. Software development methodology used is Waterfall Model, because the requirements used to develop the software is clear at the beginning. Index Terms—Flashcard, Japanese Characters, Language Learning, Spaced Repetition Software, SuperMemo